Quality Assurance and Harmonization for Targeted Biomonitoring Measurements of Environmental Organic Chemicals Across the Children’s Health Exposure Analysis Resource Laboratory Network - Kannan, Kurunthachalam (Int J Hyg Environ Health, 2021)
A consortium of laboratories established under the Children’s Health Exposure Analysis Resource (CHEAR) used a multifaceted quality assurance program to promote measurement harmonization for trace organics analyses of human biospecimens that included: (1) participation in external quality assurance (EQA) / proficiency testing (PT) programs; (2) analyses of a urine-based CHEAR common quality control (QC) pool with each analytical batch across all participating laboratories; (3) method validation against NIST Standard Reference Materials(®) (SRMs); and (4) analyses of blinded duplicates and other project-specific QC samples. The capability of five CHEAR laboratories in organic chemical analysis increased across the 4-year period, and performance in the external PT program improved over time – recent challenges reporting >90% analytes with satisfactory performance. The CHEAR QC pools were analyzed for several classes of organic chemicals including phthalate metabolites and environmental phenols by the participating laboratories with every batch of project samples, which provided a rich source of measurement data for the assessment of intra- and inter-laboratory variance. Within-laboratory and overall variabilities in measurements across laboratories were calculated for target chemicals in urine QC pools; the coefficient of variation (CV) was generally below 25% across batches, studies and laboratories and indicated acceptable analytical imprecision. The suite of organic chemicals analyzed in the CHEAR QC pool was broader than those reported for commercially available reference materials. The accuracy of each of the laboratories’ methods was verified through the analysis of several NIST SRMs and was, for example, 97±5.2% for environmental phenols and 95±11% for phthalates. Analysis of blinded duplicate samples showed excellent agreement and reliability of measurements. The intra-class correlation coefficients (ICC) for phthalate metabolites analyzed in various batches across three CHEAR laboratories showed excellent reliability (typically >0.90). Overall, the multifaceted quality assurance protocols followed among the CHEAR laboratories ensured reliable and reproducible data quality for several classes of organic chemicals. Increased participation in external PT programs through inclusion of additional target analytes will further enhance the confidence in data quality.